Private and Family Life and Contested Moralities in front of the European Court of Human Rights - Ignovska Elena (UKIM, Faculty of Law, 2023)
In fields of contested moralities, such as in the section between medically assisted reproduction and private and family life, the margin of appreciation of the European Court of Human Rights is still especially flexible, thus endangering (instead of protecting) individual human rights. The text will prove this to be the case via elaboration of two (among the others)cases: the case Paradiso and Campanelli v. Italy(2017) that involves a reproductive tourism and a lost national recognition of an adopted embryo born by surrogate woman in a foreign country and the case Orlandi and Others v. Italy(2018) that involves a lost national recognition to same-sex couples married abroad. The outcome in both cases is different. The author concludes that the European Court of Human Rights should interpret (as it does in recent cases)on grounds of rational and strict scrutiny in the European context, because its decisions set a European hierarchy of values, which cannot vary drastically from State to State. In this way, the Court should remain, for the Members of the Council of Europe, a guide, and not to allow overuse of the margin of appreciation in the field of conflicts between fundamental human rights.
Keywords: human rights, private and family life,contested moralities,European Convention of Human Rights, European Court of Human Rights.